Evidence of a Viable Pool of Stem Cells within Human Osteoarthritic Cartilage - Nelson, Larissa (Cartilage, 2014)
OBJECTIVES: Osteoarthritis (OA) is a debilitating disease affecting more than 4 million people in the United Kingdom. Despite its prevalence, there is no successful cell-based therapy currently used to treat patients whose cartilage is deemed irrecoverable. The present study aimed to isolate stem cells from tibial plateaux cartilage obtained from patients who underwent total knee replacements for OA and investigate their stem cell characteristics. DESIGN: Clonally derived cell lines were selected using a differential adhesion assay to fibronectin and expanded in monolayer culture. Colony forming efficiencies and growth kinetics were investigated. The potential for tri-lineage differentiation into chondrogenic, osteogenic, and adipogenic phenotypes were analyzed using histological stains, immunocytochemistry, and reverse transcriptase polymerase chain reaction. RESULTS: Colony forming cells were successfully isolated from osteoarthritic cartilage and extensively expanded in monolayer culture. Colony forming efficiencies were consistently below 0.1%. Clonal cell lines were expanded beyond 40 population doublings but disparities were observed in the number of population doublings per day. Clonally derived cell lines also demonstrated in vitro multilineage potential via successful differentiation into chondrogenic, osteogenic, and adipogenic lineages. However, variation in the degree of differentiation was observed between these clonal cell lines. CONCLUSIONS: A viable pool of cells with stem cell characteristics have been identified within human osteoarthritic cartilage. Variation in the degree of differentiation suggests the possibility of further subpopulations of cells. The identification of this stem cell population highlights the reparative potential of these cells in osteoarthritic cartilage, which could be further exploited to aid the field of regenerative medicine.